Emotions of Mothers whose Preterm Infant was Discharged from The Neonatal Intensive Care Unit: A Qualitative Study - Merter, Ozlem Selime; Şimşek, Didem Coşkun (My University, 2025)
Objective: This study aims to determine the emotions of mothers whose preterm infants were discharged from the Neonatal Intensive Care Unit. Methods: This study was conducted using a phenomenological design, one of the qualitative research methods. It was conducted with 17 mothers who had preterm infants born between 28-32 weeks of gestation in the NICU between March and September 2022. Semi-structured interviews were conducted with mothers. A one-on-one in-depth interview technique was used to collect data. All interviews were audio recorded and transcribed. The audio recordings recorded during the interviews were evaluated using the traditional content analysis of Graneheim and Lundman. The study was written based on the COREQ checklist. Results: As a result of the content analysis, three main themes were determined in the study: (1) fear (fear of losing the infant, harming the infant and having the infant go back to the Neonatal Intensive Care Unit), (2) worry (worrying of not being able to intervene, worrying that the infant will get sick, worry of making a mistake, (3) happiness (emotion of motherhood). Conclusion: It has been determined that the discharge of the preterm infant affects maternal health intensely, especially in the emotional field. The findings showed that mothers had post-discharge counseling needs. The discharge training, which will be given to mothers in practice on infant care, will have important contributions in the home care process
Keywords: Mothers; Preterm birth; emotions; nurses; discharge.